Impact of the European proposal to restrict PFAS on modern medical technology and treatment options - Derad Lukas; Thaler Melanie; Wiktor Kevin; Bregulla Rainer; Bader Christian (Current Directions in Biomedical Engineering)
Functionality of state-of-the-art medical devices often depends on high-end materials. Today, a large spectrum of medical devices like heart valves, vascular grafts, sutures or endoscopic devices consist of or incorporate fluoropolymers like polytetrafluoroethylene (PTFE). Fluoropolymers offer unique mechanical, electrical and chemical properties. Based on their chemical constitution, fluoropolymers are assigned to the group of per- and polyfluorinated substances (PFAS). The aim of the current restriction proposal within Europe (EU) is to limit and/or fully ban the persistent PFAS substances known as forever chemicals. The restriction proposal concerns all PFAS substances beyond further subdividing and evaluating their hazardous potential and with just short-term derogations depending on the application. The consequences of the impending restriction proposal on PFAS is shown from a medical device industry viewpoint. Literature data on annual material consumption and supply chain are collected and evaluated, especially pointing to future problems assuming an entry into force of the pending restriction proposal. Furthermore, the short derogation times are contextualized with current timelines of Medical Device Regulation (MDR) approval processes to highlight the impact on product availability assuming a PFAS ban. Selected examples of affected products illustrate, how patient treatment options are limited by the PFAS restriction. It can be clearly shown that the PFAS restriction will critically affect the medical device sector through collapsed supply chain and insufficient derogation times for product approvals, thus limiting the availability of medical products and setting back the gold standards in medical treatment.